Factors Associated with Malaria Prevention Actions Based on the Health Belief Model in the Working Area of Pagurawan Health Center, Medang Deras District, Batubara Regency, 2025 - Evalina, Ita; Frida Lina Tarigan; Mindo Tua Siagian; Donal Nababan; Henny Arwina Bangun (JURNAL KESMAS DAN GIZI (JKG), 2025)
Malaria transmission occurs in tropical countries. Malaria cases continue to be a widespread global health issue in nearly all parts of the world. Malaria prevention can be achieved by changing public perceptions about the dangers of malaria infection through behavioral approaches, one of which is the Health Belief Model (HBM). The purpose of this study is to analyze factors associated with malaria prevention actions based on the Health Belief Model in the working area of the Pagurawan Health Center, Medang Deras District, Batubara Regency, in 2025. This research is descriptive-analytic with a cross-sectional study design. The study was conducted in the working area of the Pagurawan Health Center, Medang Deras District, Batubara Regency, from July 2024 to February 2025. The sample size was 100 respondents, selected through proportional sampling. The results of the study revealed significant relationships with perceived susceptibility (p value 0.000), perceived severity (p value 0.023), perceived benefits (p value 0.002), perceived barriers (p value 0.000), and cues to action (p value 0.000). The most dominant variable was cues to action with an Exp(B) of 14.285.